The impact of sport on health status, psychological well‐being and physical performance of adults with haemophilia. (24th May 2016) - von Mackensen, S.; Harrington, C.; Tuddenham, E.; Littley, A.; Will, A.; Fareh, M.; Hay, C. R. M.; Khair, K.
Abstract : Background: There is increasing recognition that sport is important for individuals with haemophilia; however, there remains a paucity of data of the importance of this in adults, many of whom already have joint pathology related to childhood bleeds and treatment access. This multicentre, cross‐sectional study presents the impact of sport on health‐related quality of life (HRQoL), physical performance and clinical outcomes in adults with haemophilia. Results: Fifty adults aged 35.12±14.7 with mild ( n = 12), moderate ( n = 10), or severe ( n = 28) haemophilia A (70%) or B (30%) from four haemophilia centres across the United Kingdom participated in the study. A total of 64% were overweight/obese according to their BMI; median orthopaedic joint scores using the WFH Orthopaedic Joint Score (OJS) were 6 (range 0–48). On a VAS pain scale (range of 0–10), patients reported mean score of 5.66 ± 2.4. 36% of participants reported not doing any sport, mainly due to their physical condition. However, 64% of participants reported undertaking sporting activity including contact sports, mostly twice per week in average 4 h week −1 . Participating in sport did not have a statistically significant impact on HRQoL; except in the domain 'sport and leisure' of the Haem‐A‐QoL. Patients doing more sport reported significantly better HRQoL than those doing less sport ( P < 0.005). Those doing sport for more than 4 h week −1 had a significantly better physical performance than patients doing less sport (assessed with Hep‐Test‐Q). Encouraging physical activity and sport in older patients with haemophilia may have a direct impact on their HRQoL; thus, education about sport activity should be incorporated into routine haemophilia care.